Business process pattern for improving social sustainability - Thorsten Schoormann; Marco Di Maria (Australasian Journal of Information Systems)
Business process management (BPM) has the ability to boost transformations towards sustainable entities by innovating organizational structures. While the majority of existing BPM tools and methods focus on economic obligations, social sustainability is often underrepresented. This is problematic because it inhibits business improvement of people’s quality of life (e.g., health and equity), fails to address changing customer demands beyond transactional excellence, and obstructs the consideration of new regulations. Based on a literature review and expert interviews, recurrent problems and best practice solutions for integrating social sustainability into business processes were collected. These were formalized into a set of process patterns and then evaluated through illustrative demonstrations, an applicability check, and interviews with process experts. The paper proposes ten patterns together with a series of examples to guide the analysis and improvement of processes in terms of social sustainability. They support both generating novel ideas and identifying weaknesses. In doing this, our work complements existing tools and methods from sustainable BPM, advances the current body of knowledge in this stream, and opens avenues for a more holistic consideration of sustainability in business processes.